Uma ferramenta colaborativa para utilização de técnicas de criatividade no processo de elicitação de requisitos - Negreiros, Robson Cavalcante de (2016)
The research in Software Engineering (SE) and specifically in the area of Requirements Engineering (RE) focused on creativity has gained space because of the distribution of knowledge in Creativity in several other disciplines. Assuming that ER is an activity that is Collaborative in its essence and that allows the Creative Resolution of Problems, this work proposes the application of a Cognitive Models for Creative Problem Solving (CPS) in the creation of a collaborative process, in order to promote the development of the a tool called ORIGAMI. This work will discuss how the analysis of creativity techniques is supported by the tool, defines a collaborative process to work on creative problem solving and collaboration at the time of requirements elicitation and reports the development of the oRIGAmI tool to support the Brainstorming creative technique. To evaluate the tool, the objective was to carry out scenarios of use and application of a Focus Group to identify the support in the activity of elicitation with a focus on the available functionalities and potential collaborative potential. The results obtained in the conclusion of this work was the identification of creativity techniques for development in a collaborative tool, to provide an alternative to work the CPS in a virtual collaborative environment and the benefits of a collaborative tool of creativity in the process of Requirements Elicitation when the participants are geographically distributed.